The European Autonomous Definition of a Worker and its Implications for the Self-Employed in the Sphere of Individual and Collective Labour Law - Unterschütz, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
Currently, there is no clear definition valid throughout Europe that makes a clear distinction between genuine self-employed workers who work independently of a contractor and false self-employed workers. The 2006 ILO Recommendation takes a broad approach to the concept of “employment relationship” to enable action to be taken against false self-employment. In determining whether an employment relationship exists, the primary focus should be on the facts of the worker’s activity and remuneration, regardless of how the relationship is characterised in the contract. The EU’s so-called autonomous definition of a worker, as established by the CJEU, contains three main criteria to establish the existence of an employment relationship: whether the person performing the work acts under direction, the nature of the work (e.g. whether it is real, effective and regular) and whether remuneration is received for the work. Recent judgments of the CJEU lead to the conclusion that such a deﬁnition should be applied in all Member States in order to guarantee the eﬀectiveness of employment law directives. This line of interpretation is further reinforced by the reference to the autonomous deﬁnition of worker in Directive 2019/1152 z on transparent and predictable working conditions in the European Union. The aim of the publication is to reﬂect on whether the application of this deﬁnition would mean that individual and collective labour law rights would also be extended to the ostensibly self-employed.